Managerial Ownership and Managerial Ability on Tax Avoidance: Moderating Role of Firm Size - Saida Rahma, Syifa; ., Masripah (KnE Social Sciences, 2024)
This research aims to empirically investigate the impact of managerial ownership and managerial competence on tax avoidance, along with examining how firm size moderates these relationships. The study utilized panel data linear regression with a fixed effects approach, employing purposive sampling from 87 manufacturing firms in Indonesia spanning the years 2019 to 2021, totaling 261 firm years. The analysis reveals that managerial ownership does not influence tax avoidance, while managerial competence demonstrates a positive association with tax avoidance. Additionally, the findings suggest that neither firm size nor its interaction with managerial ownership and ability significantly affects the practice of tax avoidance. Keywords: firm size, managerial ability, managerial ownership, tax avoidance